In-silico design of a new multi-epitope vaccine candidate against SARS-CoV-2 - Abbas Alibakhshi; Armina Alagheband Bahrami; Elmira Mohammadi; Elmira Mohammadi; Shahrzad Ahangarzadeh; Meysam Mobasheri (Acta Virologica, 2024)
Frequent, and sometimes more dangerous, mutations in SARS-CoV-2 indicate that a stronger strategy is needed to produce an effective vaccine—a vaccine that contains a wider range of virus factors and remains effective if one or more mutations have occurred in a part of the genome. In this study, four important virus proteins were used to make a multi-epitope protein vaccine. For this purpose, antigenic determinant of 4 proteins were selected and a protein structure was designed using 4 domains containing epitopes. After examining its antigenic potential, its three-dimensional structure was designed and then docked with immune system receptors. Finally, using the dynamic molecular (MD) simulation, complexes and interactions were investigated and their interaction energies were measured. The results of the study showed that the designed structure has good relative stability and interacts well with its receptors and can be used as a vaccine candidate for further studies.